PREVENTIVE MEASURES TO REDUCE PEDESTRIAN TRAFFIC ACCIDENTS IN DEVELOPING URBAN ENVIRONMENTS - Odilov Odiljon Zokirjonovich (European Science Publishing, 2025)
Pedestrian traffic accidents represent a significant public health and urban planning challenge, particularly in developing cities where infrastructure, enforcement, and behavioural systems are often underdeveloped. This paper examines the root causes of pedestrian-related accidents and identifies key preventive measures tailored for rapidly urbanising environments. Through a comparative analysis of global best practices and local case studies from Central Asia, the research proposes a multi-dimensional framework combining infrastructural redesign, legal reinforcement, intelligent transport systems, and community engagement. Findings highlight the importance of pedestrian-prioritised planning, data-driven decision-making, and public education in reducing accident rates. The study concludes with strategic policy recommendations to support safer pedestrian mobility in low-resource urban contexts.
Keywords: Pedestrian safety, traffic accidents, developing cities, urban mobility, road infrastructure, accident prevention, intelligent transport systems, urban planning, public health, traffic law enforcement.